Cultural Diversity and Human Resource Management in Multinational Companies - Flavian Clipa; Raluca Irina Clipa (CES Working Papers, 2009)
When the multinational firms employ human resources from different countries they have to submit to the restrictions concerning cultural differences. The paper is an attempt to show how the human resource management administrates these cultural differences.
Keywords: 330; diversity; cultural differences; human resources management; multinational company; multiculturality